Application of Modal Analysis for the Vibrational Comfort Investigation on Board Ships: a Case Study - Rognoni, Giovanni; Mažeika, Pranas; D’Amore, Giada Kyaw Oo; Brocco, Emanuele; Mickevičienė, Rima; Žapnickas, Tomas; Iamshchikov, Evgenii; Djačkov, Vasilij; Biot, Marco (Journal of marine science and application, 2024)
The design of a ship is a process facilitated by different parallel departments. Specialists from various disciplines jointly work on a project, eventually covering the entire process. Though simultaneously, these disciplines are often subject to a hierarchy, either clearly defined or dictated by necessity. Within these branches, despite a growing interest in enhancing the comfort on board ships, noise and vibration design is among the most sacrificed. Compared to hydrodynamic or structural modifications, efforts devoted to improving vibrational comfort are generally slightly impactful and costly. Consequently, these improvements are often relegated to the final stages of the design procedure. The underestimation of noise and vibrational comfort design can generate serious, unexpected issues emerging only in the advanced phases of the ship’s life, and post-construction interventions are often needed. This case is exemplified in the current study, where the crew of the research vessel Mintis, a catamaran-type hull, reported discomfort in the navigation wheelhouse. A measurement campaign was set up to assess the complaints of the operating personnel regarding the high vibrational levels. Subsequent to the measurements, a numerical simulation, specifically comprising a modal analysis, was conducted to investigate the nature of the disturbance and distinguish the underlying mechanism at its origin. This paper meticulously presents and discusses the strategy undertaken to analyze and solve the vibrational problem encountered on board, with particular attention to the criteria and the modeling considerations adopted.